Performance Evaluation of the Gradient Diffusion Strip Method and Disk Diffusion Method for Ceftazidime–Avibactam Against Enterobacterales and Pseudomonas aeruginosa: A Dual-Center Study - Zhang, Jingjia; Li, Gang; Zhang, Ge; Kang, Wei; Duan, Simeng; Wang, Tong; Li, Jin; Huangfu, Zhiru; Yang, Qiwen; Xu, Yingchun; Jia, Wei; Sun, Hongli (Frontiers in Microbiology, 2021)
Objectives: Ceftazidime–avibactam is a novel synthetic beta-lactam + beta-lactamase inhibitor combination. We evaluated the performance of the gradient diffusion strip method and the disk diffusion method for the determination of ceftazidime–avibactam against Enterobacterales and Pseudomonas aeruginosa. Methods: Antimicrobial susceptibility testing of 302 clinical Enterobacterales and Pseudomonas aeruginosa isolates from two centers were conducted by broth microdilution (BMD), gradient diffusion strip method, and disk diffusion method for ceftazidime–avibactam. Using BMD as a gold standard, essential agreement (EA), categorical agreement (CA), major error (ME), and very major error (VME) were determined according to CLSI guidelines. CA and EA rate > 90%, ME rate < 3%, and VME rate < 1.5% were considered as acceptable criteria. Polymerase chain reaction and Sanger sequencing were performed to determine the carbapenem resistance genes of all 302 isolates. Results: A total of 302 strains were enrolled, among which 182 strains were from center 1 and 120 strains were from center 2. A percentage of 18.21% (55/302) of the enrolled isolates were resistant to ceftazidime–avibactam. The CA rates of the gradient diffusion strip method for Enterobacterales and P. aeruginosa were 100% and 98.65% (73/74), respectively, and the EA rates were 97.37% (222/228) and 98.65% (73/74), respectively. The CA rates of the disk diffusion method for Enterobacterales and P. aeruginosa were 100% and 95.95% (71/74), respectively. No VMEs were found by using the gradient diffusion strip method, while the ME rate was 0.40% (1/247). No MEs were found by using the disk diffusion method, but the VME rate was 5.45% (3/55). Therefore, all the parameters of the gradient diffusion strip method were in line with acceptable criteria. For 31 blaKPC, 33 blaNDM, 7 blaIMP, and 2 blaVIM positive isolates, both CA and EA rates were 100%; no MEs or VMEs were detected by either method. For 15 carbapenemase-non-producing resistant isolates, the CA and EA rates of the gradient diffusion strips method were 100%. Whereas the CA rate of the disk diffusion method was 80.00% (12/15), the VME rate was 20.00% (3/15). Conclusion: The gradient diffusion strip method can meet the needs of clinical microbiological laboratories for testing the susceptibility of ceftazidime–avibactam drugs. However, the VME rate > 1.5% (5.45%) by the disk diffusion method. By comparison, the performance of the gradient diffusion strip method was better than that of the disk diffusion method.